Vertrauen, Opportunismus, Kontrolle: Eine empirische Analyse von Joint Venture Beziehungen vor dem Hintergrund der Transaktionskostentheorie. - Eberl, P; Kabst, Rüdiger (Managementforschung.)

A honeypot for the exploration of spammers' behaviour - Schryen, Guido (IATAC IAnewsletter)

An e-mail honeypot addressing spammers' behavior in collecting and applying addresses - Schryen, Guido (Proceedings of the 6th IEEE Information Assurance Workshop)
Spam has become one of the most annoying and costly phenomenon in the Internet. Valid e-mail addresses belong to the most valuable resources of spammers, but little is known about spammers? behavior when collecting and harvesting addresses and spammers? capabilities and interest in carefully directed, consumer-oriented marketing have not been explored yet. Gaining insight into spammers? ways to obtain and (mis)use e-mail addresses is useful in many ways, e.g. for the assessment of the effectiveness of address obscuring techniques and the usability and necessity of hiding e-mail addresses on the Internet. This paper presents a spam honeypot project in progress addressing these issues by systematically placing e-mail addresses in the Internet and analyzing received e-mails. The honeypot?s conceptual framework, its implementation, and first empirical results are presented. Finally, an outlook on further work and activities is provided.
Keywords: Spam; ham; e-mail; honeypot; address obscuring technique; address taxonomy

Dynamic Load Balancing in Distributed Hash Tables - Bienkowski, Marcin; Korzeniowski, Miroslaw; Meyer auf der Heide, Friedhelm (Peer-to-Peer Systems IV)

Page Migration in Dynamic Networks - Bienkowski, Marcin; Meyer auf der Heide, Friedhelm (Mathematical Foundations of Computer Science 2005)

A Web Computing Environment for Parallel Algorithms in Java - Bonorden, Olaf; Gehweiler, Joachim; Meyer auf der Heide, Friedhelm (Proceeedings of 6th International Conference on Parallel Processing and Applied Mathematics (PPAM))
We present a web computing library (PUBWCL) in Java that allows to execute strongly coupled, massively parallel algorithms in the bulk-synchronous (BSP) style on PCs distributed over the internet whose owners are willing to donate their unused computation power. PUBWCL is realized as a peer-to-peer system and features migration and restoration of BSP processes executed on it. The use of Java guarantees a high level of security and makes PUBWCL platform independent. In order to estimate the loss of efficiency inherent in such a Java-based system, we have compared it to our C-based PUB-Library.

Load Balancing Strategies in a Web Computing Environment - Bonorden, Olaf; Gehweiler, Joachim; Meyer auf der Heide, Friedhelm (Proceeedings of 6th International Conference on Parallel Processing and Applied Mathematics (PPAM))
We compare different load balancing strategies for Bulk-Synchronous Parallel (BSP) programs in a web computing environment. In order to handle the influence of the fluctuating available computation power, we classify the external work load. We evaluate the load balancing algorithms using our web computing library for BSP programs in Java (PUBWCL). Thereby we simulated the external work load in order to have repeatable testing conditions. With the best performing load balancing strategy we could save 39% of the execution time averaged and even up to 50% in particular cases.

Towards Automated Chaos Verification - Day, Sarah; Junge, Oliver; Mischaikow, Konstantin (EQUADIFF 2003)

Transport in Dynamical Astronomy and Multibody Problems - Dellnitz, Michael; Junge, Oliver; Koon, Wang Sang; Lekien, Francois; Lo, Martin W.; Marsden, Jerrold E.; Padberg, Kathrin; Preis, Robert; Ross, Shane D.; Thiere, Bianca (International Journal of Bifurcation and Chaos)
We combine the techniques of almost invariant sets (using tree structured box elimination and graph partitioning algorithms) with invariant manifold and lobe dynamics techniques. The result is a new computational technique for computing key dynamical features, including almost invariant sets, resonance regions as well as transport rates and bottlenecks between regions in dynamical systems. This methodology can be applied to a variety of multibody problems, including those in molecular modeling, chemical reaction rates and dynamical astronomy. In this paper we focus on problems in dynamical astronomy to illustrate the power of the combination of these different numerical tools and their applicability. In particular, we compute transport rates between two resonance regions for the three-body system consisting of the Sun, Jupiter and a third body (such as an asteroid). These resonance regions are appropriate for certain comets and asteroids.

Transport of Mars-Crossing Asteroids from the Quasi-Hilda Region - Dellnitz, Michael; Junge, Oliver; Lo, Martin W.; Marsden, Jerrold E.; Padberg, Kathrin; Preis, Robert; Ross, Shane D.; Thiere, Bianca (Physical Review Letters)